A One-Step Electrochemical Aptasensor Based on Signal Amplification of Metallo Nanoenzyme Particles for Vascular Endothelial Growth Factor - Mei, ChenYang; Zhang, Yuanyuan; Pan, Luting; Dong, Bin; Chen, Xingwei; Gao, Qingyi; Xu, Hang; Xu, Wenjin; Fang, Hui; Liu, Siyu; McAlinden, Colm; Paschalis, Eleftherios I.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, a one-step electrochemical aptasensor was developed for the detection of the biomarker vascular endothelial growth factor (VEGF), an important protein in the pathogenesis of many retinal diseases including age-related macular degeneration, diabetic retinopathy, retinopathy of prematurity, and retinal vein occlusion. The aptamer has a good affinity and can rapidly identify and capture VEGF based on its unique structure. We designed a VEGF aptasensor based on the aptamer recognition and complex metallo nanoenzyme particles as an electron exchange center and bridge between capture DNA and electrode. The aptamers maintain the hairpin structure to avoid nonspecific surface adsorption and expose the capture sequence outwards when the target was inexistent. Conversely, the aptamers opened the hairpin structure to release space to accomplish binding between VEGF and DNA, and resulted in increased impedance. The performance of the electrochemical aptasensor is detected by electrochemical impedance spectroscopy (EIS). The limit of detection by EIS was as low as 8.2 pg mL-1, and the linear range was 10 pg mL-1 – 1 μg mL-1. The electrochemical aptasensor also showed high specificity and reproducibility.